1987
DOI: 10.1016/s0022-5347(17)43258-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Urinary Stone Inhibitors on Membrane Interaction Potentials of Stone Crystals

Abstract: The effect of stone growth inhibitors (citrate, pyrophosphate, ethane diphosphonate, methane diphosphonate, chondroitin sulfate A, chondroitin sulfate C, heparin and ribonucleic acid) on crystal-membrane interactions of whewellite, weddellite, apatite, brushite, struvite, uric acid, monosodium urate and quartz (control) stones was quantitated. As a model for the initial retention of microcrystals by kidney epithelial membranes, crystal-induced membranolysis of red blood cells served as a measure of crystal-mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Removal of GAGs from epithelial cell sur faces promoted crystal adhesion and the process was reversed by treatment of denuded cell surfaces with sul fated polysaccharides, heparin and CS [36]. CaOx crystal induced membranolysis of red blood cells was also inhib ited by treatment with heparin and CS [72], Pretreatment of CaOx crystals with sulfated GAGs prevented their adherence to the LLC-PK1, and MDCK cells in culture [102], Heparin also prevented endocytosis of CaOx crys tals by BSC-1 monkey kidney epithelial cells but by an interaction with cells and not crystals [69], Cell-surface GAGs are hypothesized to provide a pro tective barrier against crystals and solutes and act as gen eralized antiadherence factor. Moreover, highly charged GAGs coating both the crystals and cell surfaces may pre vent crystals from interacting with the cells through elec trostatic repulsion.…”
Section: Crystal Adherence To Renal Epithelial Cellsmentioning
confidence: 99%
“…Removal of GAGs from epithelial cell sur faces promoted crystal adhesion and the process was reversed by treatment of denuded cell surfaces with sul fated polysaccharides, heparin and CS [36]. CaOx crystal induced membranolysis of red blood cells was also inhib ited by treatment with heparin and CS [72], Pretreatment of CaOx crystals with sulfated GAGs prevented their adherence to the LLC-PK1, and MDCK cells in culture [102], Heparin also prevented endocytosis of CaOx crys tals by BSC-1 monkey kidney epithelial cells but by an interaction with cells and not crystals [69], Cell-surface GAGs are hypothesized to provide a pro tective barrier against crystals and solutes and act as gen eralized antiadherence factor. Moreover, highly charged GAGs coating both the crystals and cell surfaces may pre vent crystals from interacting with the cells through elec trostatic repulsion.…”
Section: Crystal Adherence To Renal Epithelial Cellsmentioning
confidence: 99%
“…Two polymorphs of calcium oxalate, calcium oxalate monohydrate (COM) 3 and calcium oxalate dihydrate (COD), are the most abundant mineral types, but others may exist in smaller amounts, including calcium phosphate minerals. It has been reported that the occurrence of COM, the more thermodynamically stable polymorph of calcium oxalate, is often at the core of most kidney stones and is approximately twice as frequent as COD (2), although both crystal types typically exist to some degree in most stones (3,4). COM is commonly found in the urine of "stone formers," but seldom is seen in healthy urine; on the other hand, COD crystals are typically found in the urine of both healthy people and stone formers and are routinely excreted during urination (5)(6)(7).…”
mentioning
confidence: 99%
“…Calcium oxalate can crystallize in three different hydrate forms: COM, COD, and CaOx trihydrate crystals ( 7 ). Among these, COM crystals are the most common form of CaOx crystals present in urinary calculi in humans compared to COD crystals ( 23 , 24 ). To investigate whether a monoclonal anti-TGFβ IgG antibody can directly influence CaOx crystal formation, we pre-incubated Na 2 C 2 O 4 (sodium oxalate) with the anti-TGFβ IgG or the control IgG1 antibody followed by addition of CaCl 2 (calcium chloride) to form CaOx crystals in vitro .…”
Section: Resultsmentioning
confidence: 99%